A DFT-based model on the adsorption behavior of H2O, H+, Cl−, and OH− on clean and Cr-doped Fe(110) planes - Hu, Jun (2018)
The impact of four typical adsorbates, namely H2O, H+, Cl−, and OH−, on three different planes, namely, Fe(110), Cr(110) and Cr-doped Fe(110), was investigated by using a density functional theory (DFT)-based model. It is verified by the adsorption mechanism of the abovementioned four adsorbates that the Cr-doped Fe(110) plane is the most stable facet out of the three. As confirmed by the adsorption energy and electronic structure, Cr doping will greatly enhance the electron donor ability of neighboring Fe atoms, which in turn prompts the adsorption of the positively charged H+. Meanwhile, the affinity of Cr to negatively charged adsorbates (e.g., Cl− and O of H2O, OH−) is improved due to the weakening of its electron donor ability. On the other hand, the strong bond between surface atoms and the adsorbates can also weaken the bond between metal atoms, which results in a structure deformation and charge redistribution among the native crystal structure. In this way, the crystal becomes more vulnerable to corrosion.